EFFECTIVENESS OF TAMARIND LEAF (Tamarindus indica L.) ETHANOL EXTRACT ANTIBACTERIAL AGAINST Porphyromonas gingivalis - Yemima Putri Wijaya Baiin; Henry Y. Mandalas; Vinna Kurniawati Sugiaman (FKG Unlam, 2023)
ABSTRACTBackground: One of the initial measures to prevent chronic periodontitis is the use of mouthwash. Chlorhexidine is an antibacterial agent that can be used as a mouthwash. Chlorhexidine has side effects so that a new method is needed to prevent periodontitis with fewer side effects, namely by using plants as a medicine, one of the plants containing active compounds with antibacterial effects. The ethanol extract of tamarind leaf is proven to contain active compounds of flavonoids, tannins, alkaloids, and saponins. Purpose: The aim of the study was to analyze the antibacterial effect of ethanol extract of tamarind leaf (Tamarindus indica L.) leaf against Porphyromonas gingivalis bacteria. Material and methods: The research is an experimental laboratory type using the disc diffusion method (Kirby-Bauer), namely the paper disc diffusion method with the test material of ethanol extract of tamarind leaf (Tamarindus indica L.) in various concentrations, namely: 3.125%, 6.25%, 12.5 %, 25%, 50%, and 100%. Results: Based on the results of the research on the antibacterial effect of the ethanolic extract of tamarind leaf with concentrations of 3.125%, 6.25%, and 12.5% with an average diameter of 0.00 mm of inhibition zone. At concentrations of 25%, 50%, and 100%, they fall into the medium criteria group, because they have an average inhibition zone diameter of 5.21 mm, 7.45, and 9.16 mm, so that the concentration of 100% is closest to the average the mean diameter of the positive control group or chlorhexidine. Conclusion: It can be concluded that the ethanol extract of tamarind leaf (Tamarindus indica L.) has an antibacterial effect that can inhibit the growth of Porphyromonas gingivalis bacteria at a concentration of 100% with an average inhibition zone diameter of 9.16 mm. Keywords: Antibacterial, Porphyromonas gingivalis, Tamarind leaf